2016
DOI: 10.1093/brain/awv397
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive imaging of oxygen extraction fraction in adults with sickle cell anaemia

Abstract: Sickle cell anaemia is a monogenetic disorder with a high incidence of stroke. While stroke screening procedures exist for children with sickle cell anaemia, no accepted screening procedures exist for assessing stroke risk in adults. The purpose of this study is to use novel magnetic resonance imaging methods to evaluate physiological relationships between oxygen extraction fraction, cerebral blood flow, and clinical markers of cerebrovascular impairment in adults with sickle cell anaemia. The specific goal is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
130
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 95 publications
(143 citation statements)
references
References 47 publications
10
130
3
Order By: Relevance
“…We demonstrate that more than 96% of the variability in blood R 2 can be described by a bilinear model using hematocrit and the squared oxygen extraction, even with hematocrit values into the teens. We further demonstrate that existing T 2b calibrations are highly inaccurate for hematocrits below 30% and should not be used in anemic patient populations . In fact, the commonly used bovine calibration has sizable bias even for patients with normal hematocrit values.…”
Section: Discussionmentioning
confidence: 83%
“…We demonstrate that more than 96% of the variability in blood R 2 can be described by a bilinear model using hematocrit and the squared oxygen extraction, even with hematocrit values into the teens. We further demonstrate that existing T 2b calibrations are highly inaccurate for hematocrits below 30% and should not be used in anemic patient populations . In fact, the commonly used bovine calibration has sizable bias even for patients with normal hematocrit values.…”
Section: Discussionmentioning
confidence: 83%
“…Recent demonstration that OEF is globally increased in SCD, likely reflects ongoing compensation for oxygen metabolic stress. 31 Furthermore, acute ischemic lesions have been identified on brain MRIs in children with SCD experiencing an acute decrease in oxygen delivery, such as in splenic sequestration or aplastic crisis. 32 …”
Section: Discussionmentioning
confidence: 99%
“…It should also be noted that many patients were in no to little pain during our experiments, meaning they were in a relatively stable condition. Recent studies have also shown that during resting state, SCD patients have increased cerebral blood flow compared to healthy controls to compensate for decreased oxygen levels so that oxygen delivery at rest is normal (Bush et al, 2016, Jordan et al, 2016). This suggests fMRI measurements should be normal during rest in SCD patients.
Fig.
…”
Section: Methodsmentioning
confidence: 99%